Heavy metals (Cr, Pb, Cd, Ni) in aerosols emitted from electronic cigarettes sold in Malaysia - Ting, Chuo Yew; Ahmad Sabri, Nawaltul Akma; Tiong, Lee Len; Zailani, Hazalinawati; Wong, Li Ping; Aghamohammadi, Nasrin; Anchah, Lawrence (Taylor & Francis, 2020)
While past studies have detected heavy metals in aerosols emitted from electronic cigarettes (ECIG), they have provided little information detailing the practical implications of the findings to the Malaysian population due to variations between products. The aims of this study were to analyse heavy metals of interest (HMOI) in the aerosols emitted from selected ECIG and to evaluate potential health risks by referring to the permissible daily exposure (PDE) from inhalational medications defined by the United States Pharmacopeia Chapter 232. All four HMOI were detected in aerosols emitted from the selected ECIG in Sarawak. Among the four, Cr was present at the highest median levels (6.86 ng/m3), followed by Ni (0.30 ng/m3), Pb (0.19 ng/m3) and Cd (0.01 ng/m3). Five out of 100 combinations (5%) of ECIG and ECIG liquids were found to emit Cr that exceed the recommended PDE. Future studies examining more heavy metal variants, using a larger sample size and different analytical techniques to compare various ECIGs are recommended. © 2019, © 2019 Taylor & Francis Group, LLC.